Implementasi Kebijakan Reforma Agraria Di Kecamatan Jenawi Kabupaten Karanganyar (Studi Asset Reform Dan Acces Reform) - Joko Suranto, Sularna & (JI@P, 2017)
Land reform is the Agrarian Reform Program launched by the Indonesian Government. The program is implemented for the structural arrangement of domination and ownership of the land. This is done to ensure the right to agrarian resources through land reform or asset reform and broader development efforts which involves multiple participants to ensure that the land assets that have been given can grow productively and sustainably or access reform. The purpose of this study was to describe the implementation of agrarian reform policy in the district Jenawi, Karanganyar. The importance of achieving the goal of this study was that the success of an activity is determined by the quality of the process and indicators that have been set. This study was descriptive kualitatf research which combines the implementation model of Donald S. Van Meter, Carl E. Van Horn, and Edward III. Data collection techniques that used in this study was interviews and review of document. Determination of informants by using purposive sampling. Informants in this study came from Land Agency Office of Karangayar, the District Head Jenawi, and the villager of Anggrasmanis. Based on the study results, it was concluded that agrarian reform policies have been implemented properly in District Jenawi, Karanganyar. Both implementers and the target group in these activities have known and understand the standards and target activities. Land Agency Office of Karanganyar still understaffed of gauge in terms of implementation of asset reform. This is because the number of employees of measure is not comparable with the land area that must be done. Meanwhile, in the terms of implementation of acces reform, human resources which is own is considered to be adequate. Mentoring and counseling to the community programs that has been prepared can be done well and get a positive response from the target group, so it can be formed a good cooperation. A positive attitude shown by the whole range of implementers, so that a positive response was also obtained from the target group. Agrarian reform activities in the district of Jenawi Karanganyar has accordance with Budget Implementation Registration Form 2014, the technical instructions, and legislation which serve as guidelines. The purpose of agrarian reform in the District Jenawi especially the Village Anggrasmanis has been perceived by society as well as a positive impact in their lives. Key words: Standards and Objectives Policy, Resonances, Communication, Disposition, Bureaucratic structure.